Genus Picrasma: A comprehensive review on its ethnopharmacology, phytochemistry and bioactivities. (15th November 2021) - Xu, Wen-Hui; Liang, Zong-Suo; Su, Xiao-Min; He, Run-Xi; Liang, Qian
Abstract: Ethnopharmacological relevance: The genus Picrasma belongs to the Simaroubaceae family and contains six species which are mainly distributed in tropical and subtropical regions of Asia and America. The barks, roots, stems, branches, or leaves of several Picrasma species have been applied as folk medicines to treat fever, sore throat, dysentery, eczema, nausea, loss of appetite, diabetes mellitus, cancer, and hypertension. Aim of the study: A systematic summary on the botanic characterization, ethnopharmacological uses, phytochemistry, bioactivities and toxicity of species belonging to Picrasma was presented to facilitate the exploitation of the therapeutic potential of these plants. Materials and methods: The literatures about Picrasma were retrieved from a series of scientific search engines including Web of Science, SciFinder, PubMed, CNKI, Google Scholar, Elsevier, Wiley, ACS publications, and SpringerLink between 1970 and 2020. Plant names were validated by "The Plant List" (www.theplantlist.org ). Results: As ethnopharmacological uses, Picrasma species are valuable folk medicines to treat fever, inflammation, dysentery, eczema, cancer, diabetics, skin infection, and so on. Up to now, a total of 361 compounds including 126 alkaloids, 132 quassinoids, 67 triterpenoids, and 36 miscellaneous compounds were reported from Picrasma species. Quassinoids and alkaloids are the principal constituents in the genus. The extracts and phytochemical constituents of Picrasma species demonstrate a wide range of bioactivities including cytotoxic, anti-inflammatory, antimicrobial, and other activities. Conclusions: Picrasma species are widely used as traditional medicines, have diverse chemical constituents with obvious biological activities. Nevertheless, further studies are required on the Picrasma species to assert the ethnopharmacological uses, clarify their bioactive constituents, determine pharmacological actions, and toxicity. Therefore, the present review may provide a critical clue for future studies and further exploitations on Picrasma species. Graphical abstract: Image 1 Highlights: A review to summarize the ethnopharmacological uses, phytochemistry, bioactivities, toxicity of genus Picrasma. Up to 2020, a total of 361 compounds were reviewed from Picrasma species. The extracts, fractions, and isolated compounds of Picrasma species possessed diverse bioactivities. The links between ethnopharmacological uses, phytochemistry, bioactivities, toxicity have been discussed.